Response of Pelagic Calcifiers (Foraminifera, Thecosomata) to Ocean Acidification During Oligotrophic and Simulated Up-Welling Conditions in the Subtropical North Atlantic Off Gran Canaria - Lischka, Silke; Stange, Paul; Riebesell, Ulf (Frontiers in Marine Science, 2018)
Planktonic Foraminifera and thecosome pteropods are major producers of calcite and aragonite in the ocean and play an important role for pelagic carbonate flux. The responses of planktonic foraminifers to ocean acidification (OA) are variable among the species tested and so far do not allow for reliable conclusion. Thecosome pteropods respond with reduced calcification and shell dissolution to OA and are considered at high risk especially at high latitudes. The present investigation was part of a large-scale in situ mesocosm experiment in the oligotrophic waters of the eastern subtropical North Atlantic. Over 62 days, we measured the abundance and vertical flux of pelagic foraminifers and thecosome pteropods as part of a natural plankton community over a range of OA scenarios. A bloom phase was initiated by the introduction of deep-water collected from approx. 650 m depth simulating a natural up-welling event. Foraminifers occurred throughout the entire experiment in both the water column and the sediment traps. Pteropods were present only in small numbers and disappeared after the first two weeks of the experiment. No significant CO2 related effects were observed for foraminifers, but cumulative sedimentary flux was reduced at the highest CO2 concentrations. This flux reduction was most likely accompanying an observed flux reduction of particulate organic matter (POM) so that less foraminifers were intercepted and transported downward.